Performance of Islamic Education and Civic Education Teachers in Improving Students’ Character Education in SMAN 10 Banda Aceh - Maghfirah, Maghfirah; Khairuddin, Khairuddin; Usman, Nasir (FKIP Universitas Lampung, 2021)
This research aims to determine the ability of teachers in the planning, implementating and evaluating the learning outcomes. This research uses a qualitative approach with descriptive method. Data was collected through interviews, observation and documentation study. The subjects of the study are the school principal, vice principal in the curriculum division, student representatives and teachers.The results of the study show that: (1) The ability of teachers to plan character-based learning so far has had an impact on the development of attitudes and teaching methods of teachers (2) The implementation of character-based learning has a positive impact on the improvement of the character for whole students. However, teachers have less skilled in choosing and utilizing media, learning resources, the methods to support character-based learning goals.The teacher is unfamiliar to using multimedia learning media, (3) Evaluation of character-based learning outcomes for students give an excellent result related to the level of change that happen to the students, but there are also students who still need special attention and guidance in order to shape the character.Keywords: character education, teacher performance, islamic education, civic education.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202118